Perancangan Sistem Informasi Akuntansi Upah Lembur Karyawan Menggunakan Extreme Programming - Setiawansyah; Sulistiani, Heni; Yuliani, Asri; Hamidy, Fikri (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
The production department of PT Sugar Labinta requires overtime to complete its work. This overtime work process requires procedures and calculations. One of the problems that is often faced is too many employees who work overtime (overtime) and limited resources to manage and calculate overtime pay. The staff section in calculating employee overtime pay must look at the employee overtime work order (SPKL) one by one so that it takes a long time, then input the employee overtime hours, basic salary, calculate overtime hours manually, and calculate overtime pay and total wages overtime, this requires accuracy so that if an error occurs it will be detrimental to employees and the calculation of overtime pay will be recalculated. This designed information system can make it easier for companies to calculate employee overtime wages and reduce errors in calculating overtime pay and validating overtime wage data. By using the extreme programming method, it can be more effective in the process because it can produce applications with a performance efficiency level of 75% of the planned target time. The results of the employee overtime wage accounting information system make it easier for the company to make journal reports on cash disbursements for employee overtime wages at PT Sugar Labinta.